A thematic study of the Hadith "La darar wa la dirar" regarding environmental balance: https://doi.org/10.5281/zenodo.17102163 - Muhammad Ajmal; Sadheer Khan (Mufti Muhammad Hassan); Awais Ud din Khan (Journal of Religion and Society, 2025)
This article, "A Thematic Study of the Hadith 'La Dharar wa La Dhirar' Regarding Environmental Balance," explores the comprehensive framework that the Prophetic Hadith "La Dharar wa La Dhirar" (Neither inflict harm nor tolerate harm) provides for environmental protection and balance in Islam. It argues that Islam, as a religion aligned with nature, offers guidance for all aspects of life, including ecological well-being. The study delves into the causes of environmental degradation, identifying human actions, such as ignorance, selfishness, and the lack of fear of God, along with the industrial revolution and its consequences, as primary contributors to ecological imbalance. It discusses specific forms of damage including land, air, and water pollution, and the environmental impacts of warfare. Furthermore, the article highlights Islamic solutions for environmental protection based on the Hadith. These solutions encompass principles for water conservation and purity, sustainable land management through afforestation, importance of cleanliness and proper waste management, and ethical guidelines during wartime that prohibit environmental destruction. The study also examines the deeper dimensions of Islamic environmental ethics, such as the concept of humans as Allah's vicegerents (Khilafah) on Earth, the notion of natural resources as a trust (Amanah), the interconnectedness of all creation glorifying Allah, the responsibility of governance and the state in ensuring a healthy environment, and the alignment of Islamic principles with sustainable development. In conclusion, the article asserts that the Hadith "La Dharar wa La Dhirar" forms the foundation of the Islamic concept of environmental balance, not only prohibiting harm but also encouraging positive actions for environmental betterment. It proposes that Islamic teachings offer a holistic approach for humanity to live in a sustainable and healthy environment, with individuals, society, and the state all playing their part. This principle is presented as both a moral and religious obligation, crucial for human survival and welfare. Keywords: La darar wa la dirar, Environmental Balance, Islamic Environmental Ethics, Harm Prevention, Stewardship (Khalifah)